Exaggerated follicular helper T-cell responses in patients with LRBA deficiency caused by failure of CTLA4-mediated regulation - BARIŞ, SAFA (MOSBY-ELSEVIER, 2018)
Background: LPS-responsive beige-like anchor protein (LRBA) and cytotoxic T lymphocyte-associated antigen 4 (CTLA4) deficiencies give rise to overlapping phenotypes of immune dysregulation and autoimmunity, with dramatically increased frequencies of circulating follicular helper T (cTFH) cells. Objective: We sought to determine the mechanisms of cTFH cell dysregulation in patients with LRBA deficiency and the utility of monitoring cTFH cells as a correlate of clinical response to CTLA4-Ig therapy. Methods: cTFH cells and other lymphocyte subpopulations were characterized. Functional analyses included in vitro follicular helper T (TFH) cell differentiation and cTFH naive B-cell cocultures. Serum soluble IL-2 receptor a chain levels and in vitro immunoglobulin production by cultured B cells were quantified by using ELISA. Results: cTFH cell frequencies in patients with LRBA or CTLA4 deficiency sharply decreased with CTLA4-Ig therapy in parallel with other markers of immune dysregulation, including soluble IL-2 receptor a chain, CD45RO(+)CD4(+) effector T cells, and autoantibodies, and this was predictive of favorable clinical responses. cTFH cells in patients with LRBA deficiency were biased toward a TH1-like cell phenotype, which was partially reversed by CTLA4-Ig therapy. LRBA-sufficient but not LRBA-deficient regulatory T cells suppressed in vitro TFH cell differentiation in a CTLA4-dependent manner. LRBA-deficient TFH cells supported in vitro antibody production by naive LRBA-sufficient B cells. Conclusions: cTFH cell dysregulation in patients with LRBA deficiency reflects impaired control of TFH cell differentiation because of profoundly decreased CTLA4 expression on regulatory T cells and probably contributes to autoimmunity in patients with this disease. Serial monitoring of cTFH cell frequencies is highly useful in gauging the clinical response of LRBA-deficient patients to CTLA4-Ig therapy.
Keywords: Autoantibodies; LPS-responsive beige-like anchor; cytotoxic T lymphocyte-associated antigen 4; regulatory T cells; follicular helper T cells; follicular regulatory T cells; SYSTEMIC-LUPUS-ERYTHEMATOSUS; IMMUNE DYSREGULATION; MUTATIONS; AUTOIMMUNITY; CTLA-4; DIFFERENTIATION; DISEASE; PHENOTYPE; EXPANSION; PROMOTE